Effect of Noni Fruit Extract (Morinda citrifolia) on Glucose Intake to Diabetes Mellitus White Rat Muscle Tissue - Patricia Wulandari (Eureka Herba Indonesia, 2020)
Noni fruit (Morinda citrifolia) is one of the most common plants in Indonesia. This plant is often found in various regions in Indonesia, where these plants are often in the form of shrubs or wild plants that grow in yards or plantations. This study aims to assess the effect of noni (Morinda citrifolia) fruit extract on blood sugar levels and the expression of GLUT4 protein in muscle tissue which shows the potential of the test extract's ability to improve blood glucose intake in cells so that it can maintain blood sugar regulation. This research was an experimental study that used white rats as research subjects. Induction of diabetes was done by injecting alloxan at a dose of 110 mg/kg BW intraperitoneally; then the white rats were given 10% glucose to drink. Alloxan-induced white rats showed a very significant increase in blood sugar levels, where the use of the drug metformin was able to reduce blood sugar levels significantly. In white rats induced with diabetes mellitus, there was a decrease in GLUT4 levels in muscle tissue. The administration of metformin drugs or noni fruit extracts shows the ability to increase levels of GLUT4 protein. In conclusion, noni fruit extract affects lowering blood sugar levels in diabetes mellitus white rats by increasing glucose intake in cells and tissues.